Analysis of regional unemployment using regression models featuring spatial and temporal correlation of variables - Konopásek, Martin; Formánek, Tomáš; Černý, Michal; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2023)
The relations between macroeconomic variables distributed over time and space could be very complex. Therefore, when performing empirical analysis, it is important to take into account as many assumed features of the examined variables as possible. This masters thesis describe advanced econometric methods incorporating spatial and temporal features to effective evaluation and quantification of properties and relationships within examined variables. The main contribution of this paper is introduction of dynamic panel regression model that account for numerous features that one could expect within modelled relationships and provides estimation procedure to obtain consistent estimation of corresponding parameters. Since this model is new to the available literature, custom R implementation of corresponding estimation procedure is provided as well. This model allows for modeling spatial and temporal dynamics, as well as spatially heterogeneous responses while using endogenous regressors in one framework. All described procedures are then applied to unemployment rates in selected European countries.
Vedoucí práce: Tomáš Formánek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: ekonometrie a operační výzkum [obor dipl. práce]; diplomové práce; master's theses